The Role of the Human Capital and Managerial Skills in Explaining the Productivity Gaps between East and West - Wolfgang Steffen; Johannes Stephan (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2007)
This paper assess determinants of productivity gaps between firms in the European transition countries and regions and firms in West Germany. The analysis is conducted at the firm level by use of a unique database constructed by field work. The determinants tested in a simple econometric regression model are focussed upon the issue of human capital and modern market-oriented management. The results are novel in as much as a solution was established for the puzzling results in related research with respect to a comparison of formal qualification between East and West. Furthermore, the analysis was able to establish that the kind of human capital and expertise mostly needed in the post-socialist firms are related to the particular requirements of a competitive marketbased economic environment. Finally, the analysis also finds empirical support for the role of capital deepening in productivity catch-up, as well as the case that the gaps in labour productivity are most importantly rooted in a more labour-intense production, which does not give rise to a competitive disadvantage. – – Diese Arbeit stellt Determinanten der Produktivitätslücke zwischen Firmen in europäischen Transformationsländern und westdeutschen Regionen fest. Durchgeführt wird die Analyse auf Unternehmensebene unter Nutzung einer speziellen Datenbasis, die durch Feldforschung erstellt wurde. Die Determinanten, getestet in einem einfachen ökonometrischen Regressionsmodell, sind auf die Problematik Humankapital und modernes, marktorientiertes Management ausgerichtet. Die Studie führte zu ganz neuen Ergebnissen und einer Lösung für die unerklärlichen Resultate ähnlicher Studien in Bezug auf einen Vergleich formaler Bedingungen in Ost und West. Darüber hinaus wurde in der Untersuchung post-sozialistischer Firmen festgestellt, dass Humankapital und Fachwissen bezogen auf die besonderen Anforderungen einer wettbewerblichen, marktbasierten ökonomischen Umwelt am meisten gebraucht wird. Schließlich wird die Rolle der verbesserten Kapitalausstattung im Aufholprozess der Produktivität empirisch bestätigt. Weiterhin zeigt sich, dass die Diskrepanz in der Arbeitsproduktivität im wesentlichen durch eine arbeitsintensivere Produktion begründet wird, was allerdings nicht zu einem Wettbewerbsnachteil führt.
urn:nbn:de:gbv:3:2-4644
Keywords: L6; M2; 330; productivity gap; Central East Europe; East Germany; firm-level analysis; Produktivität; Arbeitsproduktivität; Humankapital; Führungskräfte; Qualifikation; Vergleich; Neue Bundesländer; Alte Bundesländer; Deutschland; Polen; Tschechische Republik; Ungarn